Immobilization of the glucose isomerase from Caldicoprobacter algeriensis on Sepabeads EC-HA and its efficient application in continuous High Fructose Syrup production using packed bed reactor. (30th March 2020) - Neifar, Sawssan; Cervantes, Fadia V.; Bouanane-Darenfed, Amel; BenHlima, Hajer; Ballesteros, Antonio O.; Plou, Francisco J.; Bejar, Samir
Graphical abstract: Highlights: The GICA was immobilized onto amino supports with very high recovery yield. The adsorbed GICA showed an improvement on its thermo-stability. An excellent operational stability in batch reactor cycles was observed at 85 °C. A continuous packed bed reactor system was established for HFS production at 70 °C. Abstract: The glucose isomerase GICA from Caldicoprobacter algeriensis was immobilized by ionic adsorption on polymethacrylate carriers (Sepabeads EC-EA and EC-HA) or covalent attachment to glyoxal agarose. The Sepabeads EC-HA yielded the highest recovery of activity (89%). The optimum temperature and pH of immobilized GICA were 90 °C and 7.0, respectively, similar to the corresponding values of free enzyme. Nevertheless, the adsorbed enzyme displayed higher relative activity at acidic pH, greater thermostability, and better storage stability, compared to the free form. Moreover, the immobilized enzyme showed an excellent operational stability, in 15 successive 3 h reaction cycles at 85 °C under a batch reactor, preserving 83% of its initial activity. Interestingly, a continuous process for High Fructose Syrup (HFS) production was established with the adsorbed GICA using a packed bed reactor during eleven days at 70 °C. HPAEC-PAD analysis showed a maximum bioconversion rate of 49% after 48 h of operation.